First Report of Fusarium Wilt of Basil Caused by Fusarium oxysporum f. sp. basilici in Argentina - Lori, Gladys Albina (2014)
Annually, ~20 ha of sweet basil (Ocimum basilicum L.) are cultivated in greenhouses in the green belt area surrounding La Plata, Argentina, mainly for fresh consumption. In 2004 to 2007, basil plants of cv. Genovese showed wilt symptoms, necrosis of leaves and stems, asymmetrical growth, and discolored vascular tissue in greenhouses in La Plata. In 2007, the same symptoms were observed on plants of cv. Morada grown from seeds that were produced in Italy. Isolations were completed from root, crown, and stem sections of diseased plants of cv. Genovese from three greenhouses in 2004 to 2007, and from commercial seeds, stem sections, flowers, and seeds of diseased plants of cv. Morada in 2007. Seeds and portions of symptomatic tissues were surfacedisinfested with 0.5% NaOCl for 1 min, rinsed in sterilized distilled water, air dried, and plated on 2% potato dextrose agar (PDA). Twentyseven isolates were identified as Fusarium oxysporum Schltdl. based on morphological characteristics, and the species identification confirmed by PCR assay using a F. oxysporum f. sp. basilicispecific primer pair, Bik 1 and Bik 2.